2023
DOI: 10.1002/advs.202207269
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Piezoelectric Sensitivity of Amino Acid Crystals by Mechanical Annealing for the Engineering of Fully Degradable Force Sensors

Abstract: Biodegradable piezoelectric force sensors can be used as implantable medical devices for monitoring physiological pressures of impaired organs or providing essential stimuli for drug delivery and tissue regeneration without the need of additional invasive removal surgery or battery power. However, traditional piezoelectric materials, such as inorganic ceramics and organic polymers, show unsatisfactory degradability, and cytotoxicity. Amino acid crystals are biocompatible and exhibit outstanding piezoelectric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 65 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…After being encapsulated by polylactide (PLA), the piezoelectric voltage can be obviously output after implantation in animals. There are many studies on the preparation of the piezoelectric structure of amino acids, but most of the applications for the use of amino acid piezoelectric properties are in biosensors, 86,88–91 while there are relatively few in medical therapies. There are a few research studies focusing on the application of amino acids for wound treatment, but none of them use their piezoelectric properties.…”
Section: Piezoelectric Effect and Piezoelectric Materialsmentioning
confidence: 99%
“…After being encapsulated by polylactide (PLA), the piezoelectric voltage can be obviously output after implantation in animals. There are many studies on the preparation of the piezoelectric structure of amino acids, but most of the applications for the use of amino acid piezoelectric properties are in biosensors, 86,88–91 while there are relatively few in medical therapies. There are a few research studies focusing on the application of amino acids for wound treatment, but none of them use their piezoelectric properties.…”
Section: Piezoelectric Effect and Piezoelectric Materialsmentioning
confidence: 99%
“…Choosing conductive polyaniline and polylactic acid to package mechanical-annealed Ile crystals, the prepared piezoelectric sensors generate an open circuit voltage of more than 0.4 V under an applied force of 100 N. In addition, due to its excellent biocompatibility and biodegradability, the packaged force sensors can be used to monitor muscle contraction and lung respiration in vivo and work steadily for up to 4 weeks. 211 Hydrogen bonds, as one of the main driving forces, play an essential role in producing amino acid based supramolecular self-assembly. 39 Ji et al reported a typical example of the hydrogen-bonded face-to-face dimers in L-Tyr crystals, which mediate the formation of tightly packed, rigid, low-symmetrical packing.…”
Section: Applications Of Amino Acid Based Materialsmentioning
confidence: 99%
“…It is noteworthy that the piezoelectric constant of mechanical-annealed Ile crystals is 12 times that of its crystal powders (Figure b). Choosing conductive polyaniline and polylactic acid to package mechanical-annealed Ile crystals, the prepared piezoelectric sensors generate an open circuit voltage of more than 0.4 V under an applied force of 100 N. In addition, due to its excellent biocompatibility and biodegradability, the packaged force sensors can be used to monitor muscle contraction and lung respiration in vivo and work steadily for up to 4 weeks . Hydrogen bonds, as one of the main driving forces, play an essential role in producing amino acid based supramolecular self-assembly .…”
Section: Applications Of Amino Acid Based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids and peptides have been reported to obtain a variety of nanostructures, including nanofibers, nanotubes, nanowires, and nanosheets. However, their structures often show random orientations, which limits their bulk properties and potential applications. , For performance enhancements and new features, the fabrication of uniformly oriented structures is indispensable. Various methods have been adopted to fabricate unidirectionally polarized structures.…”
mentioning
confidence: 99%